Panton-Valentine leukocidin (PVL) positive methicillin resistant Staphylococcus aureus (MRSA) in raw milk in Punjab - AMANDEEP, AMANDEEP; SINGH, RANDHIR; KAUR, SIMRANPREET; GILL, J P S (The Indian Journal of Animal Sciences, 2019)
The emergence of methicillin resistant Staphylococcus aureus (MRSA) as a foodborne pathogen has posed a serious public health issue. Milk is extensively consumed food worldwide. The aim of this study was to estimate the presence of MRSA in raw milk in Punjab, by culture and polymerase chain reaction (PCR) techniques. Raw milk samples (291) were collected from all over Punjab. These 291 samples comprised 204 and 87 cow and buffalo milk samples respectively. The S. aureus was isolated on Baird Parker agar and typical colonies were subjected to biochemical tests and PCR for genus (16S rDNA) and species (nuc) specific detection. All the S. aureus isolates were further subjected to susceptibility testing to oxacillin and detection of mecA gene for methicillin resistance. Out of 291 samples, 42 (14.43%) showed contamination of S. aureus. Prevalence of S. aureus contamination was higher in cow milk (15.68%) than buffalo milk (11.49%). Only, three (1.03%) samples (one from buffalo and two from cow) were positive for MRSA. On SCC mec typing, all the MRSA positive isolates belonged to SCC mec type V, which is characteristic of Community Associated-MRSA (CA-MRSA). One isolate was also positive for pvl gene. PFGE showed that all the four isolates were closely related to each other. The results show that MRSA are present in food of animal origin and has potential to spread through it.